Nollywood in Glocal Perspective
XXV, 253 p. 12 illus., 5 illus. in color.
Keywords: 'This welcome collection both reinforces the importance of familiar films and historical trends and breaks new ground in Nollywood studies. It will be of interest to anyone eager to learn more about African screen media at the nexus of the global and the local.' — Noah Tsika, author of Nollywood Stars: Media and Migration in West Africa and the Diaspora 'Nollywood in Glocal Perspective is a valuable contribution to knowledge, providing detailed examination of Nollywood’s growth as a cultural icon with large followership and influence across Africa and the world. “The diverse perspectives provided by the contributors illuminate the local and global cultural forces that pull on the soul of Nollywood”. The collection presents a compelling and beautifully crafted, accessible, engrossing and refreshing piece which illuminates and redefines an entire area of contemporary film studies. “The authors tell Africa’s story with balance and authenticity. They celebrate Africa’s rich cultural experience and heritage; exalt in its triumphs; reflect on its struggles”. With great insight, they present Nollywood’s transition from local to glocal giant within two decades. This collection has the potential to give direction into the unexplored aesthetic and political landscape. It is a groundbreaking book, which brings new understanding, broader and more inclusive framework to look at glocalization. It is sure to become a required reading for scholars of Post-colonial Studies, Film studies and Globalization.' — Irene Isoken Agunloye, Professor of African Drama, Gender, Women & Film Studies; Director of the Centre for Gender & Women’s Studies, University of Jos, Jos, Nigeria 'Nollywood in Glocal Perspective is a compendium on film and cinema in contemporary Africa as well as a contribution to the emergent New World Entertainment Order and its diverse cultural centers. As in Los Angeles, New York City, Sydney, London, Paris or Johannesburg, there is a new (global) market for entertainment and pop culture from the African continent – Nollywood, Ghallywood, Riverwood or Bongowood -- with abundance of creative energy and feeder-talents. Like its themes and genre, the writing style is entertaining, insightful and illuminatingly gender sensitive. Nollywood in Glocal Perspective should serve as a companion to students of film, Cinema, song and dance. It is also highly recommended for stakeholders in the entertainment industry.' — Stanley Naribo Ngoa, Director, Olusegun Obasanjo Centre for African Studies (OOCAS), National Open University of Nigeria (NOUN), Abuja, Nigeria. 'Bala Musa has given media and pop culture enthusiasts and scholars a wonderful book that articulates the manner in which writers, producers, actors, actresses, business people and academicians have pulled out of the ashes of Africa, a vibrant industry that spanshundreds of cultural landscapes across the globe. The sensitivity with which the book has balanced socio-cultural values and practices with technological innovations speaks volumes about the vibrancy of the untapped creative energies from what was once known as the dark continent. Written in a friendly but scholarly style, the text provides readers with an impetus to engage critically with very well researched ideas on a growing pro-social entertainment platform.' — Faith Nguru, Author of Foreign TV Shows and Kenyan Youth 'Nollywood in Glocal Perspective is brilliant, precise and filled with such deep intellectual analysis that it deserves a reading by serious scholars of pop culture. Intellectual authority and consistency are evident throughout this seminal work. Researchers seeking conceptual and analytic frameworks on pop culture research will be delighted. Scholars seeking to understand the evolution of Nollywood (Nigeria) and its companions, Gallywood (Ghana), Riverwood (Kenya), and Bongowood (Tanzania), will be intellectually rewarded. In the anchoring piece, Bala Musa, while extolling digital technology’s seemingly empowering functions, reminds us that gender inequities and exclusions are still rampart in pop culture. Failing to address these gaps hurts the movie industry long-term.' — John Omachonu, Provost, Mars Hill University, USA.